Adoption of Information and Communication Technologies in Modern Journalism Practice Among Practitioners in Abuja (FCT) and Nasarawa State - Boma, Daniel Victoria; Kente, Josiah Sabo (Lembaga Yasin AlSys, 2025)
This study examines the adoption of information and communication technologies (ICTs) in modern journalism practice among practitioners in the Federal Capital Territory (FCT) Abuja and Nasarawa State, against the backdrop of journalism’s global transformation from manual to machine-assisted processes. Anchored in Technological Determinism Theory, the research employed a descriptive survey design, with data collected through questionnaires administered to practitioners. The findings reveal that respondents possess only moderate familiarity with ICTs for journalism, with their understanding rated as “good,” reflecting an average level of knowledge. Furthermore, the adoption and utilization of ICTs in journalism practice within the study areas remain below average, limiting efficiency in news sourcing, processing, and dissemination. The study concludes that inadequate knowledge and low adoption hinder the full benefits of ICT in journalism. It recommends sustained orientation programs and digital innovation campaigns to improve journalists’ awareness and competencies, as well as stronger government support to accelerate the transition from analogue to digital journalism. Enhanced adoption of ICTs will ultimately reduce production costs and time while improving the quality and speed of news delivery.